Assessment of women's knowledge about HPV vaccination in the light of the HPV infection as a risk factor for cervical cancer - Arkadiusz Standyło; Aleksandra Obuchowska; Justyna Wójcik; Alicja Ozga (Kazimierz Wielki University, 2020)
Introduction Cervical cancer (CC) is one of the most prevalent malignancies of female reproductive tract.  In Poland in 2017 CC accounted for 3.0% of all newly registered tumour cases among women, and was the eighth most common female malignancy.  Persistent infection with carcinogenic human papillomavirus (HPV) is the leading risk facor. Currently, it is believed that infection with the human papillomavirus (HPV), especially its oncogenic types 16 and 18, is of fundamental importance in the development of cervical cancer. Vaccination prevents from  infection with certain types of viruses, and consequently the development of cancer induced by a given type of virus. Therefore, their efficacy can be measured only in the long term, in a large cohort of vaccinated adolescents reaching the age characterized by the peak incidence of these cancers. Purpose The objective of the study was to evaluate knowledge about CC, as well as awareness of HPV and  HPV vaccination among female respondents. Material and method The research was conducted on the group of 1,260 survey respondents, who filled out the Internet questionnaire. The obtained results were analysed and checked on the basis of scientific literature. Results The percentage of respondents who select human papillomavirus infection as a risk factor for the cervical cancer is 75.9%. The onset of intercourse at an early age was considered a risk factor by only 24.6%, while a large number of sexual partners by 45.4%. Women were also asked about knowledge of HPV vaccination. Only 73.8% of them heard about it and 26.2% declare unawarness of this type of vaccination. Conclusions Health promotion campaigns and educational programs are necessary in order to reduce cervical cancer burden and should be directed particularly towards those who have demonstrated low cervical cancer knowledge and low awareness regarding HPV and its vaccine.